2012
DOI: 10.4103/1319-3767.101135
|View full text |Cite
|
Sign up to set email alerts
|

Presentation, diagnosis and outcome of predominantly hepatic Wilson′s disease in adult Saudi patients: A single centre experience

Abstract: Background/Aim:To evaluate the clinical manifestations, diagnostic features, disease course and response to treatment among Saudi adults with predominantly hepatic Wilson's disease. A retrospective cohort study of 40 adult patients diagnosed with predominantly hepatic Wilson's disease between 1994 and 2008 at King Abdulaziz Medical City, Riyadh was carried out.Patients and Methods:The diagnosis was based on varying combinations of clinical and laboratory evidence of liver disease, presence of Kayser Fleisher r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…There have been several studies on the mortality related to WD, the necessity of liver transplantation, and the prognosis of WD outside Japan 11–16 . However, few studies have reported the living conditions, such as the activities of daily living (ADL) in patients with WD 17–19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several studies on the mortality related to WD, the necessity of liver transplantation, and the prognosis of WD outside Japan 11–16 . However, few studies have reported the living conditions, such as the activities of daily living (ADL) in patients with WD 17–19 .…”
Section: Introductionmentioning
confidence: 99%
“…10 There have been several studies on the mortality related to WD, the necessity of liver transplantation, and the prognosis of WD outside Japan. [11][12][13][14][15][16] However, few studies have reported the living conditions, such as the activities of daily living (ADL) in patients with WD. [17][18][19] Furthermore, limited studies have evaluated the relationship between the factors present at diagnosis and their effect on ADL.…”
Section: Introductionmentioning
confidence: 99%